Apresiasi Sastra Indonesia di Sekolah - Maman S. Mahayana (HISKI, 2007)
The KTSP (Kurikulum Tingkat Satuan Pendidikan) gives an opportunity to teachers and schools alike in developing their own potentials. However, there should be a guarantee that tryout and evaluation are part and parcel of this opportunity, especially since it is widely known that the curriculum has undergone changesever so often. The local content as a manifestation of local potentials could be used as a rich source of teaching material by teachers and schools in developing their KTSP, especially in their teaching of Indonesian language and literature in addition, composition skills become crucial in order to balance the practice of language learning that is based on the mastery of linguistic knowledge in elementary, secondary and high schools. Students should be encouraged to appreciate literary works rather than understanding concepts. Through literary appreciation, students can develop mutual respect for each other regarding their individual opinions about literary works. Through the KTSP, both students' and teachers' freedom and creativity can be developed since the KTSP is not a holy book, but rather, a mere guideline that should be further interpreted by teachers.